PENERAPAN PROGRAM BUDAYA RELIGIUS UNTUK MENINGKATKAN KECERDASAN SPIRITUAL PESERTA DIDIK MI ATTARAQQIE PUTRI KOTA MALANG - Sholehatul Jamila; Anwar Sa’dullah; Lia Nur Atiqah Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Religious culture education has been widely applied in schools but there are still many students who tend to lack awareness in students, so there needs to be an increase in students' spiritual intelligence that can be better, religious culture has a positive impact on students in improving spiritual intelligence starting from an early age, so students are familiar with positive things that are applied in the surrounding environment. This research uses interview, observation and documentation methods. This study describes: the application of religious culture, the spiritual condition of students, the teacher's strategy, and the supporting and inhibiting factors in applying the religious culture of MI Attaraqqie Putri Malang City. The results of this study indicate that the application of religious culture programs can work well due to the supportive factors of the school environment and the need for supervision between teachers and parents, so there is no inequality in increasing students' spiritual intelligence.